Detection of high-level aminoglycoside resistance by disc diffusion and e-test amongst the enterococcus species isolated from various clinical samples in a tertiary care hospital - Paul, Manisha; Nirwan, Prem Singh; Srivastava, Preeti (International Journal of Research in Medical Sciences, 2019)
Background: The emergence of Enterococcus species in causing nosocomial infections poses a therapeutic challenge to clinicians. Enterococci are intrinsically resistance to multiple antibiotics. Acquired resistance to commonly used antibiotics like Ampicillin, Vancomycin and Aminoglycosides have made the situation worse and difficult to treat serious Enterococcal infections. The present study aimed at detection of high-level aminoglycoside resistance by disc diffusion and E-test amongst the Enterococcus species isolated from various clinical samples in a tertiary care hospital. Methods: A total of 102 Enterococcus species isolated from various clinical samples and antimicrobial susceptibility was performed by Kirby Bauer disc diffusion method as per CLSI guidelines. E-test was done for all high level aminoglycoside resistance Enterococcus species isolated by disc diffusion test. Results: Among 102 isolates, 81 were E. faecalis, 18 were E. faecium and 3 were another Enterococcus. Their antimicrobial susceptibility pattern shows all isolates were sensitive to vancomycin, linezolid and teicoplanin with HLGR, HLSR detected in 40 and 38 isolates of E. faecalis, 17 and 13 isolates of E. faecium respectively by disc diffusion whereas by E-test it was detected in 44 and 40 in E. faecalis and 17 and 14 in E. faecium respectively. E. faecium is found to be more resistance to high level aminoglycoside than E. faecalis. Conclusions: Authors hereby conclude that Enterococci being the common cause of hospital acquired infections with their increasing resistance to multiple drugs and acquisition of HLAR; it must be routinely screened for various drugs to prevent drug resistance in hospital settings for serious Enterococcal infections.